Mapping of acceleration field in FSA configuration of a LIS. (16th May 2016) - Nassisi, V.; Side, D. Delle; Monteduro, L.; Giuffreda, E.
Abstract: The Front Surface Acceleration (FSA) obtained in Laser Ion Source (LIS) systems is one of the most interesting methods to produce accelerated protons and ions. We implemented a LIS to study the ion acceleration mechanisms. In this device, the plasma is generated by a KrF excimer laser operating at 248 nm, focused on an aluminum target mounted inside a vacuum chamber. The laser energy was varied from 28 to 56 mJ/pulse and focused onto the target by a 15 cm focal lens forming a spot of 0.05 cm in diameter. A high impedance resistive probe was used to map the electric potential inside the chamber, near the target. In order to avoid the effect of plasma particles investing the probe, a PVC shield was realized. Particles inevitably streaked the shield but their influence on the probe was negligible. We detected the time resolved profiles of the electric potential moving the probe from 4.7 cm to 6.2 cm with respect to the main target axis, while the height of the shield from the surface normal on the target symmetry center was about 3 cm. The corresponding electric field can be very important to elucidate the phenomenon responsible of the accelerating field formation. The behavior of the field depends on the distance x as 1/ x 1.85 with 28 mJ laser energy, 1/ x 1.77 with 49 mJ and 1/ x 1.74 with 56 mJ. The dependence of the field changes slightly for our three cases, the power degree decreases at increasing laser energy. It is possible to hypothesize that the electric field strength stems from the contribution of an electrostatic and an induced field. Considering exclusively the induced field at the center of the created plasma, a strength of some tenth kV/m could be reached, which could deliver ions up to 1 keV of energy. These values were justified by measurement performed with an electrostatic barrier.